English-Filipino legal dictionary - Peralejo, Cesar C. (Sentro ng Wikang Filipino, University of the Philippines, 1995)
"This English-Filipino legal dictionary renders English terminology in an idiom that the Filipino majority lives and thinks in. It gives us an opportunity to discuss the meaning of the letter of the law through their own capacity to understand. Also, it makes us comprehend the law in the language where it can be better understood." These are also legal terms translated into Filipino. This is the first legal dictionary in Filipino.